1989
DOI: 10.1007/bf00146211
|View full text |Cite
|
Sign up to set email alerts
|

Do polar faculae on the sun predict a sunspot cycle?

Abstract: The paper reports the results of the analysis of the data on polar faculae for three solar cycles at the Kislovodsk Station of the Pulk0vo Observatory and on polar bright points in Ca II K line for two solar cycles (1940)(1941)(1942)(1943)(1944)(1945)(1946)(1947)(1948)(1949)(1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957) at the Kodaikanal Station of the Indian Institute of Astrophysics. We have noticed that the monthly numbers of polar faculae and polar bright points in Ca II K line and monthly sunspot areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…In this context it is interesting to note that Makarov et al (1989) and Makarov and Makarova (1996) found that the number of polar faculae observed at Kislovodsk anticipates the next sunspot cycle with a time lag of 5-6 years on average in cycles 20-22; even short term annual variations or ''surges'' of sunspot activity were claimed to be discernible in the polar facular record. An apparently conflicting result was obtained by Li et al (2002), who found using the Mitaka data base that the best autocorrelation results with a time shift of about 4 years only.…”
Section: Extending the Range Of The Polar Precursor: Early Forecasts mentioning
confidence: 99%
“…In this context it is interesting to note that Makarov et al (1989) and Makarov and Makarova (1996) found that the number of polar faculae observed at Kislovodsk anticipates the next sunspot cycle with a time lag of 5-6 years on average in cycles 20-22; even short term annual variations or ''surges'' of sunspot activity were claimed to be discernible in the polar facular record. An apparently conflicting result was obtained by Li et al (2002), who found using the Mitaka data base that the best autocorrelation results with a time shift of about 4 years only.…”
Section: Extending the Range Of The Polar Precursor: Early Forecasts mentioning
confidence: 99%
“…In other words, PNI constructed by us is in good agreement with the MWO faculae counts, but not with the NOAJ faculae counts. Furthermore, Makarov et al (1989) manually counted the polar bright points above 50 0 in both the hemispheres for the period 1940-1957 (with a data gap between 1947-1948) from KKL Ca-K spectroheliograms. They found an anti-correlation between polar bright points and sunspot number for the two cycles and suggested that Ca-K polar bright points can be used as a proxy to predict the characteristics of the next solar cycle.…”
Section: Validation Of Kkl Pni Indexmentioning
confidence: 99%
“…The magnetic field reversals at the northern and southern poles of the Sun are the phenomenon in the polar zones that imparts the cyclic nature on the solar activity [ Makarov et al , 2005]. With the use of H α synoptic charts, Makarov and Sivaraman [1989], Makarov et al [2005], and Makarov et al [2001] worked out the epochs of polar field reversal over a period of 12 solar cycles from 1872 to 2001, showing that after polar field reversal, the new appearing magnetic polarity on a hemisphere will become the leading magnetic polarity of regions at low latitudes on the same hemisphere in the following normal cycle. During the course of a sunspot cycle, namely a normal low‐latitude cycle, the trailing polarity field first cancels the field of opposite polarity left over from the previous sunspot cycle.…”
Section: Solar Full‐disk Activity Cyclementioning
confidence: 99%
“…The velocity of the poleward migration of solar activity is in range of several to tens meters per second. It is 10 to 25 m s −1 for filament activity [ Minarovjech et al , 1998b] or 4 to 29 m s −1 [ Makarov and Sivaraman , 1989], several meters per second for the green‐corona intensities [ Minarovjech et al , 2007], 7 to 20 m s −1 for the surface magnetic fields.…”
Section: Fine‐scale Characteristics Of Full‐disk Activity Cyclesmentioning
confidence: 99%